Simulation-informed learning for time-resolved angiographic contrast agent concentration reconstruction - Maul, Noah; Birkhold, Annette; Wagner, Fabian; Thies, Mareike; Rohleder, Maximilian; Berg, Philipp; Kowarschik, Markus; Maier, Andreas (Computers in Biology and Medicine, 2024)
Three-dimensional Digital Subtraction Angiography (3D-DSA) is a well-established X-ray-based technique for visualizing vascular anatomy. Recently, four-dimensional DSA (4D-DSA) reconstruction algorithms have been developed to enable the visualization of volumetric contrast flow dynamics through time-series of volumes. This reconstruction problem is ill-posed mainly due to vessel overlap in the projection direction and geometric vessel foreshortening, which leads to information loss in the recorded projection images. However, knowledge about the underlying fluid dynamics can be leveraged to constrain the solution space. In our work, we implicitly include this information in a neural network-based model that is trained on a dataset of image-based blood flow simulations. The model predicts the spatially averaged contrast agent concentration for each centerline point of the vasculature over time, lowering the overall computational demand. The trained network enables the reconstruction of relative contrast agent concentrations with a mean absolute error of 0.02±0.02 and a mean absolute percentage error of 5.31±9.25 %. Moreover, the network is robust to varying degrees of vessel overlap and vessel foreshortening. Our approach demonstrates the potential of the integration of machine learning and blood flow simulations in time-resolved angiographic contrast agent concentration reconstruction.
CRIS-Team Scopus Importer:2024-10-04
Keywords: Cerebral hemodynamics; Flow reconstruction; Image-based blood flow simulations; Intracranial blood flow; Time-resolved angiography